Emotions and personality traits as high-level factors in visual attention: a review - Kaspar, Kai; König, Peter (Frontiers in Human Neuroscience, 2012)
The visual sense has outstanding significance for human perception and behavior, and visual attention plays a central role in the processing of the sensory input. Thereby, multiple low- and high-level factors contribute to the guidance of attention. The present review focuses on two neglected high-level factors: emotion and personality. The review starts with an overview of different models of attention, providing a conceptual framework and illustrating the nature of low- and high-level factors in visual attention. Then, the ambiguous concept of emotion is described, and recommendations are made for the experimental practice. In the following, we present several studies showing the influence of emotion on overt attention, whereby the distinction between internally and externally located emotional impacts is emphasized. We also provide evidence showing that emotional stimuli influence perceptual processing outside of the focus of attention, whereby results in this field are mixed. Then, we present some detached studies showing the reversed causal effect: attention can also affect emotional responses. The final section on emotion–attention interactions addresses the interplay on the neuronal level, which has been neglected for a long time in neuroscience. In this context, several conceptual recommendations for future research are made. Finally, based on findings showing inter-individual differences in human sensitivity to emotional items, we introduce the wide range of time-independent personality traits that also influence attention, and in this context we try to raise awareness of the consideration of inter-individual differences in the field of neuroscience.